The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jafc.0c06648
|View full text |Cite
|
Sign up to set email alerts
|

High-Amylose Corn Starch/Konjac Glucomannan Composite Film: Reinforced by Incorporating β-Cyclodextrin

Abstract: Glycerol-plasticized high-amylose corn starch/konjac glucomannan (HCS/KGM) composite films incorporated with various concentrations of β-cyclodextrin (β-CD) were prepared and investigated for structural, mechanical, and physical properties. The results of X-ray diffraction, attenuated total reflectance Fourier transform infrared spectroscopy, thermogravimetric analyses, and scanning electron microscopy indicated that β-CD excluded from the polymer chains and aggregated to form crystals during film formation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The mechanical properties of the films are essential to resist external shocks and maintain the integrity of the food. 36 Tensile tests were performed on each sample film, as shown in Figure 3a. The tensile strength and Young's modulus of the CMC@Ag film were not significantly higher compared to the pure CMC film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of the films are essential to resist external shocks and maintain the integrity of the food. 36 Tensile tests were performed on each sample film, as shown in Figure 3a. The tensile strength and Young's modulus of the CMC@Ag film were not significantly higher compared to the pure CMC film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mechanical properties of the films are essential to resist external shocks and maintain the integrity of the food . Tensile tests were performed on each sample film, as shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal content of KGM was 0.3%, where a homogeneous and compact structure was formed ( Table 3 ) [ 63 ]. Interestingly, adding β-cyclodextrin (β-CD) increased the number of double-helical junction zones between starch segments particularly AM chains enhancing hydrogen bonding thereby enhance the strength of the molecular network [ 64 ]. The incorporation of β-CD into the composite film helped to reduce the phase separation, promote the interaction between the polysaccharide chains and enhancing the mechanical and barrier properties.…”
Section: Uses Of Hasmentioning
confidence: 99%
“…This promoted a more compact HCS/ KGM film. These materials were transparent and exhibited a reduced moisture formation, with an improved water vapor permeability compared with the native films [ 113 ]. Similarly, Huang et al reported the fabrication of a novel food packaging material based on molecularly imprinted polymers (MIP), using β-CD as a monomer.…”
Section: Incorporation Of Active Substances In Polymeric Matrix Composites For Active Packaging Applicationsmentioning
confidence: 99%